The “C” in crowdfunding is for co-financing: exploring participative co-financing, a complement of novel and traditional bank financing - Carolin Bock; Sven Siebeneicher; Jens Rockel (Journal of Business Economics, 2022)
We explore the potentials of participative co-financing as a means for regional banks to integrate an innovative financing technique that enhances their strengths. Our goal is to interest platform operators, decision-makers of regional banks, and researchers in the potentials of participative co-financing. We define participative co-financing as capital provision, where professional financing sources provide one part, and the other is supplied via participative crowdfunding. We claim that crowdfunding and regional banks are compatible by common interests. We explore potentials emanating at the intersection of both fields by drawing on entrepreneurship and finance literature. Eventually, we bridge the gap between both fields of research. To guide our research, we develop a framework featuring the intersection of crowdfunding and regional banks. We ask: Which potentials affect the intentions of decision-makers in regional banks to offer participative co-financing? The technology acceptance model (TAM) provides a theoretical foundation for our analysis. We conduct a twofold analysis by looking at the direct effects of potentials first and acceptance according to the TAM second. Thereby we consider the intention to offer lending- and equity-based co-financing. We surveyed decision-makers from an association of German savings banks and derived 108 answers. We show that regional banks generally accept participative co-financing as an innovative financing technique. The most likely model is lending-based co-financing, with individual persons, startups, and SMEs as target groups. Decision-makers hope to profit from cross-selling and being perceived as innovative. Nevertheless, further research and trials are necessary to advance participative co-financing.
Keywords: F65; G21; G23; R11; 650; Banking; Co-financing; Crowdfunding; Crowdinvesting; Financing; Participation